TELAAH PEMBELAAN TERPAKSA (NOODWEER) DALAM PERKARA TINDAK PIDANA PENGANIAYAAN - Halimah Annisaa; Bambang Santoso (Sebelas Maret University, 2023)
This article analyzes the field of Criminal Procedure Law related to acquittal in cases of criminal persecution at the Banyuwangi District Court. primary and secondary. The purpose of this article is to find out how judges consider deciding persecution cases that are decided loosely because they contain elements of forced defense (Noodweer). The research method used is doctrinal or normative legal research. This research is prescriptive and applied. Collection of legal materials with literature studies and legal materials used are primary and secondary legal materials. Based on the results of the study, it can be concluded that the Panel of Judges was right in deciding the case in decision Number: 462 / Pid.B / 2020 / Pn Byw which handed down a release verdict. The panel of judges held that the persecution committed by the accused was due to a forced defense (Noodweer) so that it could not be convicted, therefore the defendant must be released from all charges as stipulated in Article 191 paragraph (2) of the Code of Criminal Procedure.Keywords: Noodweer; Persecution; Justifying Reasons